The Diversity of Avifauna and Potency for Development of Ecoturism in Minangkabau Village, Padang Panjang City - Fitria Ramona; Lilis Suryani (Jurnal Biologi Universitas Andalas, 2022)
Padang Panjang has several tourist attractions surrounded by secondary forests with natural vegetation, one of them is the Minangkabau Village. The Minangkabau village has potencies to be an ecotourism object. This study aims to analyze the potential of avifauna that have an attraction for ecotourism development, determine the role of stakeholders in supporting ecotourism development in Padang Panjang, and analyze development priorities as its potencies and objects of ecotourism attraction in Padang Panjang. We used The MacKinnon method by conducting direct surveys in the field when the birds are active in the morning and evening. Deep interviews were conducted with Dinas Pemuda Olahraga dan Pariwisata (Disporapar) Kota Padang Panjang to determine stakeholders' role in tourism activities in Padang Panjang. SWOT analysis is carried out to see the priority of ecotourism development so that it is more focused and able to contribute to ecotourism areas and the community. The data obtained were analyzed to calculate the Diversity Index, Species Richness, and Species Evenness. The research results show that the Minangkabau Village areas have high diversity, richness, and evenness of bird species, namely H' 3.21, DM 7.50, and ED 0.85. There were 43 bird species from 23 families. Species that has high conservation status are Serindit Melayu (Loriculus galgulus) protected species, Jalak Kerbau (Acridotheres javanicus) with Vulnerable IUCN status, Julang Emas (Rhyticeros undulatus) Vulnerable IUCN status also protected and 2 species of Eagle (Ictinaetus malayensis and Spilornis cheela). These species have potencies to be developed as an ecotourism attraction object that stakeholders support as coaches and companions. The strategy for developing ecotourism in Padang Panjang under its potencies for biodiversity is to increase public knowledge about animal conservation (especially avifauna), biodiversity, and the adverse effects of hunting and collaborate to manage ecotourism by hiking/jungle tracking and birdwatching.